An investigation into the problems faced by grade 6 learners in answering comprehension questions: A case of Zenda Primary School in Mberengwa District. - Ndhlovu, Webster (Midlands State University, 2017)
The study sought to establish the problems faced by Grade 6 learners at Zenda Primary School in answering comprehension questions. The idea behind carrying out the research was to make sure that solutions to rectify the problems faced by Grade 6 learners were found. The research was carried out in Mberengwa District. The researcher used the case study design to carry out the study. The study used questionnaires, tests and observations to collect data. In the study ten teachers and Grade 6 pupils were used as research subjects. The research found out that the problems faced by learners in answering comprehension questions emanated from three educational stakeholders. The study found out that lack of reading materials, staff development meetings on comprehension teaching and the use of teaching media caused learners fail to answer comprehension questions. Teachers, parents and the learners are the core sources of the problems faced by learners in comprehension work. The study recommends that the school head, teachers, parents and pupils should work together in order to alleviate the problems faced by learners in comprehension writing. This can be done by regular staff development meetings and regular consultation days in which the parents and teachers meet to discuss the problems faced by pupils. The study recommends that schools should have reading culture. Teachers should use teaching and learning media when teaching comprehension. The study recommends that parents should be educated on the importance of their children’s education.